FEEDING GUILDS OF THE BIRD COMMUNITIES ON PASOSO ISLAND - Ihsan, Moh; Yusran; Ramlah, Sitti; Ningsih, Sri; Rukmi; Ramadhana, Fauziah (Forestry Study Program University Of Mataram, 2025)
Food is one of the crucial factors for the survival of birds. The interaction between habitats and birds, as well as the role of birds as environmental bioindicators, can be understood through feeding guilds by examining their responses to disturbances. This study aims to analyze the feeding guilds of bird communities on Pasoso Island. The data collection method used was the strip transect method. Data were analyzed using descriptive analysis based on bird species composition according to their guilds. The results of this study show that 33 bird species were found on Pasoso Island, classified into 10 types of feeding guilds. Based on the number of species, the insect-eating guild had the highest number (9 species) compared to other guild categories. The coastal invertebrate-eating guild and raptor guild had the fewest species, with only one species recorded in each. Regarding the number of individuals, the insect-eating guild dominated with 42 individuals, followed by the fruit-eating guild with 29 individuals. On average, the fewest individuals were found in the coastal invertebrate-eating and raptor guilds, with only one individual in each.